Fontes de energia associadas a um produto homeopático sobre balanço de energia e nitrogênio de vacas em lactação confinadas - Vieira, Diego de Sousa (2019)
The objective of this study was to evaluate the effects of energy sources associated with a homeopathic product on the energy and nitrogen balance of confined lactating cows. The experiment was conducted at the Regional Technological Development Pole of Agribusiness in Alta Mogiana, Colina-SP. Sixteen crossbred Holstein x Gir cows were used in the medium third of the lactation with an average weight of 550 kg grouped in homogeneous groups regarding milk yield, lactation period and parity, distributed in a 4x4 Latin square experimental design in factorial arrangement 2x2. The treatments consisted of concentrate with or without inclusion of 50 g / cow / day of the homeopathic product and variation of two energy sources (ground corn and citrus pulp). Ground corn as a source of energy in the diet provided the highest averages (P <0.05) for dry matter intake, weight gain, net lactation energy, intake and nitrogen secretion. There was effect of homeopathic product (P <0.05) on retention and nitrogen balance. The energy sources associated with the homeopathic product were not influenced (P> 0.05) on body weight, body condition score, net energy consumption (EL), EL maintenance, balance and efficiency of EL use. Therefore, the energy source from ground corn in the diets provides better nutrient balance in lactating cows in the middle third of lactation.